A comparison of 3 regimens to prevent nevirapine resistance mutations in HIV-infected pregnant women receiving a single intrapartum dose of nevirapine - Russell B. Van Dyke (2018)
Background. Intrapartum single-dose (SD) nevirapine (NVP) reduces perinatal transmission of human immunodeficiency virus (HIV) infection but selects for NVP-resistant virus, which compromises subsequent NVP-based therapy. A 1-week "tail" of lamivudine and zidovudine after SD-NVP decreases the risk of resistance. We hypothesized that increasing the duration or potency of the tail would further reduce this risk to <10%, using a sensitive assay to measure resistance.Methods.HIV-infected pregnant Thai women with a CD4 cell count >250 cells/μL, most receiving zidovudine, were randomized at 28-38 weeks gestation to receive 1 of 3 intrapartum and postpartum regimens: (A) zidovudine plus enteric-coated didanosine plus lopinavir and ritonavir for 7 days, (B) zidovudine plus enteric-coated didanosine for 30 days, or (C) regimen 1 for 30 days. The incidence of NVP resistance mutations at day 10 or week 6 post partum in each arm was compared with that of a historical comparison group who received prenatal zidovudine and SD-NVP. NVP resistance was identified by consensus sequencing and a sensitive oligonucleotide ligation assay (OLA). Results. At entry, the 169 participants had a median CD4 cell count of 456 cells/μL and an HIV load of 3.49 log10 copies/mL. The incidence of mutations in each of the 3 P1032 arms was 0% by sequencing and 1.8%, 7.1%, and 5.3% by OLA in arms A, B, and C, respectively, compared with 13.4% by sequencing and 29.4% by OLA in the comparison group (P <. 001 for each study arm vs comparison group). Grade 4 anemia developed in 1 woman.Conclusions.A 7-day tail of highly active combination therapy or 1 month of dual therapy after SD-NVP prevents most NVP resistance to minimal toxicity.Clinical Trials Registration.The IMPAACT P1032 Clinical Trial is NCT00109590, and the PHPT-2 Clinical Trial is NCT00398684. © 2011 The Author.